Faktor - Faktor Yang Mempengaruhi Intensitas Turnover Auditor (Studi Empiris Di Kap Big Four) - Andrea Ricardo Hutagalung (Media Riset Akuntansi, Auditing & Informasi, 2010)
Destination author conducted this research is to determine if the five factors affecting the intensity of turnover big four auditors at the accounting firm. The research method used by the author in the preparation of this paper is the method of multiple regression analysis and data collection techniques in the form of empirical studies or distributing questionnaires at four KAR Based on the analysis the authors, it can be concluded that job satisfaction, salary administration, organizational commitment, trust and professionalism of the organization does not negatively affect the intensity of turnover.Keywords : Job satisfaction, salary administration, organizational commitment, organizational trust, professionalism, the intensity of turnover.